DETERMINATION OF STANDARD TIME IN PACKAGING PROCESSING USING STOPWATCH TIME STUDY TO FIND OUTPUT STANDARD - Lukodono, Rio Prasetyo; Ulfa, Siti Kholisotul (JEMIS (Journal of Engineering & Management in Industrial System), 2017)
Time is one of the factors to assess a worker's performance in utilizing the available resources. Operator in his work requires efficient time to improve work productivity. One of factory in produce a shrimp feed in Surabaya has a large production level. In the production process, the packaging department in this company still uses human resources in their production process and the company define the standard of production without using standard time. This paper investigates the opportunity a logical analysis in determining the standard time in this company. The determination of the standard time in the packaging process requires comprehensive analysis. Objects observed are four operators in the packaging department that carried out the activities of filling bag the shrimp feed with 40 replication for each data. The work measurement was conducted by direct method using Stopwatch Time Study (STS) with snap-back method. The results of this study indicate the standard time value of the four lines packaging is not much different or almost the same. Sequentially the standard time workers line 1 to line 4 is 7.325 seconds, 7.240 seconds, 7.225 seconds, and 7.065 seconds. Allowance used for workers is 8%. However, the existing production rate of company is higher than the production rate of work measurement calculation. This is due to the difference of definition in employee allowance rate and performance rating.